Process efficiency optimisation and integration for cleaner production. (10th February 2018) - Fan, Yee Van; Varbanov, Petar Sabev; Klemeš, Jiří Jaromír; Nemet, Andreja
Abstract: Achieving and attaining sustainability of a society's existence and functioning constitutes a problem of enormous breadth, involving complex interactions among actors of varying backgrounds, personal and institutional goals. The contribution of process optimisation by engineering communities to the development of concepts and tools for improved sustainability has been substantial. This article presents an overview of process optimisation and Process Integration paradigms and the most relevant recent works, relevant to sustainability improvement. Based on this background, recent contributions to the field published in the current Special Issue of Process Integration Contribution to Cleaner Production have been analysed. The analysis shows the progress that has been made in energy and water efficiency, as well as waste management, including waste-to-energy, pollution prevention and remediation.